Ladislaus von Bortkiewicz: Statistician, economist, and a European intellectual - Wolfgang Karl Härdle; Annette B. Vogt (Humboldt University of Berlin, Collaborative Research Center 649 - Economic Risk, 2014)
Ladislaus von Bortkiewicz (1868 - 1931) was a European statistician. His scientific work covered theoretical economics, stochastics, mathematical statistics and radiology, today we would call him a cross disciplinary scientist. With his clear views on mathematical principles with their applications in these fields he stood in conflict with the mainstream economic schools in Germany at the dawn of the 20th century. He had many prominent students (Gumbel, Leontief, Freudenberg among them) and he carved out the path of modern statistical thinking. He was a true European intellectual with a career path from St. Petersburg via Gottingen to Straßburg and finally the Berliner Universität, now Humboldt-Universität zu Berlin. He is known for the precise calibration of insurance claims applying the - at that time hardly known - Poisson distribution to Prussian horse kick and child suicide data. He proposed a simple solution to the Marxian transformation problem and wrote numerous articles and books on the mathematical treatment of statistical (including radiological physical) data. In this article we sketch his life and work and point out the prominent role that he has in today's statistical thinking.
Keywords: N01; D02; B14; B16; 330; History of science; Statistics; Horse kicks; Bortkiewicz